2021
DOI: 10.1096/fj.202001830rr
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/dCas9‐mediated transposition with specificity and efficiency of site‐directed genomic insertions

Abstract: The ability and efficiency of targeted nucleases to perform sequence replacements or insertions into the genome are limited. This limited efficiency for sequence replacements or insertions can be explained by the dependency on DNA repair pathways, the possibility of cellular toxicity, and unwanted activation of proto-oncogenes. The piggyBac (PB) transposase uses a very efficient enzymatic mechanism to integrate DNA fragments into the genome in a random manner. In this study, we fused an RNA-guided catalyticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…In a recent study, the fusion of SB to the dCas9 increased the probability of insertion to a 300-bp window nearby the target site which was still far from a precise site-specific insertion event 24 . We have recently shown that by using dCas9 fused to PB and dual sgRNAs, site‐directed integrations could be achieved in 0.32% of transfected cells 14 . However, in all of the above-mentioned studies, the usefulness of these chimeric molecules for gene therapy applications is largely affected by random genomic integrations, inherent to the activity of transposase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, the fusion of SB to the dCas9 increased the probability of insertion to a 300-bp window nearby the target site which was still far from a precise site-specific insertion event 24 . We have recently shown that by using dCas9 fused to PB and dual sgRNAs, site‐directed integrations could be achieved in 0.32% of transfected cells 14 . However, in all of the above-mentioned studies, the usefulness of these chimeric molecules for gene therapy applications is largely affected by random genomic integrations, inherent to the activity of transposase.…”
Section: Discussionmentioning
confidence: 99%
“…Several previously published articles have used a similar approach to determine the efficiency of site-specific insertions 10 , 13 , 20 , 25 . In the second approach similar to our previous report 14 , we used the promoter/reporter complementation assay to register and recover cells harboring specific integrations. In this strategy, the promoterless reporter fragments can only be activated (by the endogenous promoters) when they are placed precisely in the integration site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific Cas9 mutant lacking endonuclease activity (dCas9) fused with transcriptional repressor or activation domains has also been generated to promote transcriptional inhibition or activation when coexpressed with targeted sgRNAs [ 85 , 86 ]. Lena et al fused dCas9 to PBase and targeted it to specific genomic sites using dual sgRNAs [ 87 ]. Thus, the ease of design and application of dCas9-PBase, which can edit genes at precise genomic loci, improves future medical applications.…”
Section: Characteristics Of the Pb Transposonmentioning
confidence: 99%
“…Although not yet studied outside of bacteria, CAST still holds promise for a next-generation gene editing system with enhanced efficiency [116][117][118][119].…”
Section: Castmentioning
confidence: 99%